Guidelines for Establishing and Maintaining Farm-Based Weather Stations in Haiti - Caroline G. Staub; William R. Eisenstadt; William Blanc; Nicole Monval; Clyde W. Fraisse; William Lusher; George Braun; Lee Staudt (EDIS)
Weather can significantly influence the success or failure of agricultural enterprises. Monitoring weather conditions can provide critical decision-making information. This new 4-page publication provides Haitian farmers with basic guidelines for installing and maintaining an on-farm weather station. Written by Caroline G. Staub, William Eisenstadt, William Blanc, Nicole Monval, Clyde W. Fraisse, William Lusher, George Braun, and Lee Staudt, and published by the UF/IFAS Department of Agricultural and Biological Engineering, May 2019. http://edis.ifas.ufl.edu/ae532